2021
DOI: 10.17219/pim/143975
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and statistical optimization of γ-PGA produced by Bacillus megaterium UP47 isolated from Pentaclethra macrophylla

Abstract: Odeniyi OA, Omoleye TE. Characterization and statistical optimization of γ-PGA produced by Bacillus megaterium UP47 isolated from Pentaclethra macrophylla [published online as ahead of print on December 15, 2021].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Antibacterial activity was significantly higher against gram-positive bacteria compared to gram-negative bacteria. Different Bacillus megaterium UP47-purified γ-PGA concentrations have also demonstrated antimicrobial properties against gram-negative and gram-positive pathogens ( pseudomonas aeruginosa, Klebsiella pneumoniae, shigella dysenteriae, Escherichia coli, and staphylococcus aureus ) ( Lee et al, 2014 ; Ajayeoba, 2019; Odeniyi and Omoleye, 2021 ). Odeniyi and Omoleye (2021) observed that even a low γ-PGA concentration (0.5 mg/mL) could successfully inhibit overnight cultures of E. coli, S. dysenteriae, P. aeruginosa, and S. aureus.…”
Section: Applications Of γ-Pgamentioning
confidence: 99%
“…Antibacterial activity was significantly higher against gram-positive bacteria compared to gram-negative bacteria. Different Bacillus megaterium UP47-purified γ-PGA concentrations have also demonstrated antimicrobial properties against gram-negative and gram-positive pathogens ( pseudomonas aeruginosa, Klebsiella pneumoniae, shigella dysenteriae, Escherichia coli, and staphylococcus aureus ) ( Lee et al, 2014 ; Ajayeoba, 2019; Odeniyi and Omoleye, 2021 ). Odeniyi and Omoleye (2021) observed that even a low γ-PGA concentration (0.5 mg/mL) could successfully inhibit overnight cultures of E. coli, S. dysenteriae, P. aeruginosa, and S. aureus.…”
Section: Applications Of γ-Pgamentioning
confidence: 99%